Organic solar cells using oligomer acceptors for improved stability and efficiency - Liang, Youcai; Zhang, Difei; Wu, Zerun; Jia, Tao; Lüer, Larry; Tang, Haoran; Hong, Ling; Zhang, Jiabin; Zhang, Kai; Brabec, Christoph; Li, Ning; Huang, Fei (Nature Energy, 2022)
The power conversion efficiencies of organic solar cells (OSCs) have reached over 19%. However, the combination of high efficiency and long-term stability is still a major conundrum of commercialization. Here a Y6-analogue and a 2,2′-bithiophene unit are utilized to construct a series of oligomer acceptors to investigate the effect of molecular size and packing properties on photovoltaic performance. By altering the molecular chain length, we modify the thermal properties, crystallization behaviours and molecular packing and achieve an optimal microstructure and a more stable morphology in blend films. A combination of efficiencies over 15% and an extrapolated T80 lifetime over 25,000 h, which equates to an average lifetime exceeding 16 years in Guangzhou, is achieved for binary OSCs based on an oligomer acceptor. This work emphasizes the importance of oligomeric strategy in tuning molecular packing behaviours and blend morphology, leading to development of novel non-fullerene acceptors for stable and efficient OSCs.
CRIS-Team Scopus Importer:2022-11-25